2016
DOI: 10.4049/jimmunol.1501822
|View full text |Cite
|
Sign up to set email alerts
|

Nod1 Limits Colitis-Associated Tumorigenesis by Regulating IFN-γ Production

Abstract: Chronic intestinal inflammation is a major risk factor for the development of colorectal cancer. Nod1, a member of the Nod-like receptor (NLR) family of pattern recognition receptors, is a bacterial sensor that has been previously demonstrated to reduce susceptibility of mice to chemically-induced colitis and subsequent tumorigenesis, but the mechanism by which it mediates its protection has not been elucidated. Here, we show that Nod1 expression in the hematopoietic cell compartment is critical for limiting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
4
28
1
Order By: Relevance
“…21 NODs have been studied to a greater extent in cancers of the gastrointestinal tract, such as colorectal cancer (CRC) and gastric cancer (GC), although studies in breast cancer, oral squamous cell carcinoma (OSCC), head and neck squamous cell carcinoma (HNSCC), and pancreatic cancer (PC) have also been conducted ( Table 1). Stimulation of NOD1 and NOD2 was found to be protective in inflammation-induced CRC, [69][70][71]80 whereas there was no straightforward answer as to whether activation of NOD1 in the stomach promotes or prevents the development of GC. [72][73][74] Moreover, NOD1 was found to be upregulated in PC, 79 HNSCC, 77,78 OSCC, 76 and GC, 73,74 as opposed to certain studies that reported NOD1 downregulation in the cases of OSCC 75 and GC.…”
Section: The Role Of Nod Proteins In Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…21 NODs have been studied to a greater extent in cancers of the gastrointestinal tract, such as colorectal cancer (CRC) and gastric cancer (GC), although studies in breast cancer, oral squamous cell carcinoma (OSCC), head and neck squamous cell carcinoma (HNSCC), and pancreatic cancer (PC) have also been conducted ( Table 1). Stimulation of NOD1 and NOD2 was found to be protective in inflammation-induced CRC, [69][70][71]80 whereas there was no straightforward answer as to whether activation of NOD1 in the stomach promotes or prevents the development of GC. [72][73][74] Moreover, NOD1 was found to be upregulated in PC, 79 HNSCC, 77,78 OSCC, 76 and GC, 73,74 as opposed to certain studies that reported NOD1 downregulation in the cases of OSCC 75 and GC.…”
Section: The Role Of Nod Proteins In Cancer Developmentmentioning
confidence: 99%
“…NOD1 deficiency in T cells is associated with impaired IFN-γ production and STAT1 activation. 70 NOD2 P NOD2 (or RIPK2) deficiency results in increased susceptibility to tumor formation in AOM/DSS mouse model of colon cancer. Absence of NOD2 (or RIPK2) promotes pro-inflammatory microenvironment in the intestines leading to enhanced epithelial dysplasia following chemically induced injury.…”
Section: Nod Agonists As Immunotherapeutic Agentsmentioning
confidence: 99%
“…NOD1 and NOD2 are also expressed in B and T cells, although level of expression is dependent on cellular location. There are some data to suggest that NOD1 and NOD2 ligands can enhance B and T cells after B‐cell receptor (BCR) and T‐cell receptor (TCR) engagement 105‐107 . Specifically, in human tonsillar B cells, NOD1 or NOD2 activation alone by treatment with their respective ligands was insufficient to trigger B cell activation or proliferation whereas the combination of NOD1 and NOD2 ligands and BCR activation via IgM or IgD stimulation resulted in enhanced cellular proliferation in vitro, which is further augmented by concomitant TLR stimulation 105 .…”
Section: Nod1 and Nod2 In Adaptive Immunitymentioning
confidence: 99%
“…Nonetheless, in mixed cultures of tonsillar mononuclear cells, enhanced cellular proliferation of T cells was observed after anti‐CD3/CD28 stimulation together with NOD1/NOD2 agonists although the effect was relatively weak 106 . With purified murine splenic CD3 + T cells, it was also demonstrated that NOD1 ligand can act as a co‐stimulatory molecule to enhance IFN‐γ production after stimulation with anti‐CD3 alone; however, the possibility of a contributing factor by potential contaminating antigen‐presenting cells was not ruled out 107 . Regardless, as these studies were all performed in vitro, the physiologic significance of these findings remains to be determined in vivo.…”
Section: Nod1 and Nod2 In Adaptive Immunitymentioning
confidence: 99%
“…The mechanisms through NLR-mediated effects are associated with increased CRC risk relates mainly to an excessive NLR-induced chronic pro-inflammatory microenvironment [142]. Intriguingly, NLR agonists, specially NOD1 and NOD2 agonists, have been proposed as therapeutic agents in CRC treatment because both experimental studies showed that NOD1 deficiency leads to increased tumorigenesis in mice [143] and the activation of these NLR may regulate the proinflammatory effects induced by other PRR [144,145]. Thus, although both beneficial and deleterious effects of NLR activation on CRC remains not fully understood, it seems that punctual activation or inhibition of NLR could differentially induce effects during cancer development, progression, and metastasis.…”
Section: Nucleotide Binding Oligomerization Domain-like Receptormentioning
confidence: 99%